2021
DOI: 10.3390/antiox10122005
|View full text |Cite
|
Sign up to set email alerts
|

Low Dietary n6/n3 Ratio Attenuates Changes in the NRF 2 Gene Expression, Lipid Peroxidation, and Inflammatory Markers Induced by Fructose Overconsumption in the Rat Abdominal Adipose Tissue

Abstract: The objective of this study was to examine the benefits of different n6/n3 polyunsaturated fatty acid ratios on the lipid metabolism, insulin resistance, and oxidative stress in the adipose tissue of rats fed a high-fructose diet. Male and female rats were divided into four groups: a control group (CON) (n6/n3 ratio ~7), a high-fructose group (HF) (n6/n3 ratio ~7), an N6-HF group (n6/n3 ratio ~50), and the DHA-HF group (n6/n3 ratio ~1, with the addition of docosahexaenoic (DHA) and eicosapentaenoic (EPA) acid)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Research from Roškarić et al indicated that DHA supplementation caused a significant decrease in the serum MDA concentration in comparison with the HF group. 37 Moreover, research in recent years have shown that different carbon chains and double bond numbers between DHA and EPA are the contributing factors to the different effects of DHA/EPA intervention in the anti-oxidation systems, although the underlying mechanism is still unclear. 38 In addition, a higher level of DHA in serum was negatively correlated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Research from Roškarić et al indicated that DHA supplementation caused a significant decrease in the serum MDA concentration in comparison with the HF group. 37 Moreover, research in recent years have shown that different carbon chains and double bond numbers between DHA and EPA are the contributing factors to the different effects of DHA/EPA intervention in the anti-oxidation systems, although the underlying mechanism is still unclear. 38 In addition, a higher level of DHA in serum was negatively correlated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, IL-6, and IL-1β signaling increase ROS production in the adipose tissue of obese individuals [ 37 , 237 ]. In cell cultures, 3T3-L1 adipocytes treated with TNF-α decreased the expression of antioxidants, such as GST, peroxiredoxin, and GPx, resulting in protein carbonylation, ROS generation, and mitochondrial dysfunction [ 238 , 239 ]. In adipocytes, ROS can be produced by NADPH oxidase (Nox), xanthine oxidases, and mitochondria.…”
Section: Adipose Tissue Antioxidant Defensementioning
confidence: 99%